AB0513 GLOMERULONEPHRITIS IN LEVAMISOLE-ADULTERATED COCAINE VASCULOPATHY (LACIV): A 51-CASE SERIES. (13th June 2020) - Muñoz, C.; Jaramillo Arroyave, D.; Hernandez, L.; González, L. A.; Vásquez, G.; Restrepo Escobar, M.; Urrego Callejas, T.; Vanegas, A.
Abstract : Background: Up to 88% of cocaine is tainted with levamisole, anthelmintic withdrawn from the market due to toxicity. Since 2010 LACIV patients, characterized by retiform purpura, ear necrosis, multisystemic compromise and positivity for multiple autoantibodies, have been reported. Renal involvement is the most serious and heterogeneous clinical manifestation. Objectives: To describe the renal involvement of patients with LACIV. Methods: We describe the renal manifestations of a 51 case series with LACIV admitted in four high complexity institutions in Colombia from December 2010 to December 2019. Results: All patients were mestizos, with median age of 32.5 years (SD 7.8), the male:female ratio was 4.7:1, and the time from symptoms to diagnosis 12 months (IR 32). Nephritis was found in 60.8%, with creatinine elevation in 61%, median 2.0 mg/dl (IR 3), 87% had proteinuria, median 3184 mg/day (IR 5735), 43% in nephrotic-range; 93% had hematuria and 48% pyuria and cilindruria. Biopsy was performed in 21 patients (64%), with immune complex mediated extracapillary glomerulonephritis (35%), immune complex mediated membranoproliferative glomerulonephritis (20%) pauci-immune proliferative glomerulonephritis (20%), membranous glomerulonephritis (15%), focal and segmental glomerulosclerosis (5%) and C3 mediated extracapillary glomerulonephritis (5%). Six patients (19%) developed end-stage kidney disease. Patients with nephritis had more ear necrosis, retiform purpura, leukopenia, lymphopenia, anemia, hypocomplementemia, anti-PR3 and anti-MPO antibodies, compared to patients without nephritis. Conclusion: Due to the higher abuse of cocaine and its contamination with levamisole, LACIV is an increasingly reported disease. Although skin manifestations are the most characteristic and prevalent, renal involvement is frequent, clinically and histologically heterogeneous, and potentially serious. Cytopenias, hypocomplementemia and antineutrophil cytoplasmic antibodies could identify patients at risk of nephritis References: [1]Collister D, Sathianathan C, Ryz K, Karpinski M, Bernstein K, Gibson IW. ANCA Associated Vasculitis Secondary to Levamisole-Adultered Cocaine with Associated Membranous Nephropathy: A Case Series. Am J Nephrol. 2017;45(3):209–16. [2]Carlson AQ, Tuot DS, Jen K-Y, Butcher B, Graf J, Sam R, et al. Pauci-immune glomerulonephritis in individuals with disease associated with levamisole-adulterated cocaine: a series of 4 cases. Medicine (Baltimore). 2014 Oct;93(17):290–7. Disclosure of Interests: None declared